Can artificial intelligence change the face of orthopaedic surgery? current and future concepts - Mustafa, Mohammad; Ahmed, Nasir; Ain, Noor ul; Najjad, Kazim Rahim; Noor, Syed Shahid (Journal of the Pakistan Medical Association, 2026)
Orthopaedic surgery has evolved remarkably into a highly specialised and advanced medical field. The discipline has seen substantial improvements in surgical techniques and the development of subspecialties. Outcomes can vary widely, with some procedures not yielding the expected improvement in quality of life. This variability in outcomes leads to inconsistencies in the standard of care. Artificial intelligence emerges as a powerful tool to bridge gaps in knowledge and standardise care across the orthopaedic field. Artificial intelligence can assist in various aspects of orthopaedic surgery, such as image recognition, risk assessment and clinical decision-making. However, the implementation of artificial intelligence in orthopaedics is not without challenges. The reliance on large datasets raises concerns about data ownership, privacy and the potential for algorithmic bias. As artificial intelligence continues to evolve, its role in orthopaedics will likely expand, offering new opportunities to optimise patient care and improve the overall quality of healthcare. Key Words: Artificial intelligence, Orthopaedic, Surgery, Healthcare system.